The Preacher's complete homiletical commentary: (on an original plan) (Funk & Wagnalls Co., 1892)
[I] Genesis / J.S. Exell and T.H. Leale -- [II] Exodus / J.S. Exell -- [III] Leviticus / W.H. Jellie, assisted by F.W. Brown. Numbers, chapters I to XV / W. Jones -- [IV] Numbers, chapters XVI to XXXVI / W. Jones. Deuteronomy / J. Wolfendale -- [V] Joshua / F.G. Marchant -- [VI] Judges / J.P. Millar -- [VII] Ruth / W. Baxendale. Samuel / W. Harris -- [VIII] Kings / G. Barlow -- [IX] Chronicles / J. Wolfendale. Ezra / W. Jones. Nehemiah, chapters I to VI / W.H. Booth, J.H. Goodman, and S. Gregory -- [X] Nehemiah, chapters VII to XIII / W.H. Booth, J.H. Goodman and S. Gregory. Esther / W. Barrows. Job / T. Robinson -- [XI-XII] Psalms / W.L. Watkinson [and others] 2 v -- [XIII] Proverbs / W. Harris -- [XIV] Ecclesiastes / T.H. Leale. Song of Solomon / T. Robinson -- [XV-XVI] Isaiah / R.A. Bertram and A. Tucker. 2 v. -- [XVII] Jeremiah / W.H. Jellie -- [XVIII] Lamentations / G. Barlow. Ezekiel / D.G. Watt, T.H. Leale and G. Barlow -- [XIX] Daniel / T. Robinson -- [XX] Minor prophets / J. Wolfendale -- [XXI] Index to the commentary on the Old Testament -- [XXII] St. Matthew / W.S. Lewis and H.M. Booth -- [XXIII] St. Mark / J.H. Burn -- [XXIV] St. Luke / J. Willcock -- [XXV] St. John / W.F. Scott -- [XXVI] Acts / T. Whitelaw -- [XXVII] Romans / W. Burrows -- [ XXVIII] Corinthians / H.J. Foster -- [XXIX] Galatians, Ephesians, Philippians, Colossians, I. and II. Thessalonians / G. Barlow -- [XXX] Timothy, Titus, Philemon / G. Barlow. Hebrews and St. James / R. Tuck -- [XXXI] I.